2022
DOI: 10.3389/fmed.2022.894465
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Pancreatic Steatosis and Indices of Insulin Resistance After Metabolic Surgery

Abstract: PurposeObesity is associated with fat accumulation in ectopic sites such as the pancreas, the so-called pancreatic steatosis (PS). Bariatric surgery has been shown to be associated with reducing pancreatic fat. This study investigated the effect of laparoscopic sleeve gastrectomy (LSG) on pancreatic volume and its fat content and glucose homeostasis.MethodsThe study enrolled 54 patients subjected to LSG. Metabolic variables and pancreatic exocrine function were assessed immediately before surgery and 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…It has also demonstrated that bariatric surgery can lead to significant reductions in fat accumulation within the pancreas. 124 Nonetheless, education regarding healthy dietary habits and regular exercise should be the mainstay for reducing the NAFPD risk, as well as for treating those already diagnosed with it.…”
Section: Treatment Of Nafpdmentioning
confidence: 99%
“…It has also demonstrated that bariatric surgery can lead to significant reductions in fat accumulation within the pancreas. 124 Nonetheless, education regarding healthy dietary habits and regular exercise should be the mainstay for reducing the NAFPD risk, as well as for treating those already diagnosed with it.…”
Section: Treatment Of Nafpdmentioning
confidence: 99%
“…Bariatric surgery has a proven effect on type 2 diabetes improvement ( 1 ). Several studies have shown a reduction in pancreatic fat accumulation following bariatric surgery, an effect that might improve glucose homeostasis ( 13 , 59 , 60 ). Accordingly, an amelioration of pancreas steatosis together with a downregulation of the lipogenic genes Srebf1, Mogat2 and Dgat1 was observed following sleeve gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Salman (n = 54) после выполнения продольной резекции желудка доля жировой ткани в ПЖ уменьшилась с 26,8 ± 7,2 % до 20,0 ± 7,3 %, а также определялось существенное снижение активности панкреатической липазы плазмы (р < 0,001). Кроме того, была замечена положительная корреляция между процентом общей потери массы тела и уменьшением доли жира в ПЖ (r = 0,295, р = 0,030) [34].…”
Section: рисунокunclassified